Divergent litter traits of riparian plant species between humid and drier biomes within the tropics. Issue 2 (28th December 2022) - Sena, Guilherme; Tonin, Alan M.; Caliman, Adriano; Callisto, Marcos; Hamada, Neusa; Hepp, Luiz U.; Kowalczuk, Vânia L.; Martins, Renato T.; Medeiros, Adriana O.; Morais, Paula B.; Moretti, Marcelo; Moretto, Yara; et al.
Abstract : Riparian forests provide abundant plant litter – mostly in the form of dead leaves (hereafter litter) – for both forest soils and adjacent stream ecosystems, supporting terrestrial and aquatic detritus‐based food webs. Although the fate of litter is predominantly dependent on its chemical and physical traits, there is limited availability of data on those traits over large spatial scales or empirical comparisons of traits across tropical biomes. We filled this gap by exploring the differences and similarities of nine litter traits and their dependence on phylogenetics for 68 plant species from riparian forests across three continental‐scale, South American biomes: Amazon, Atlantic Forest and Cerrado. All three biomes produced litter with similar percentages of carbon (C) and phosphorus (P), C:P mass ratios, specific leaf area and toughness. However, litter from the driest biome (Cerrado) was better defended chemically (higher phenolic content) and had lower nutritional quality (higher C:nitrogen [N] mass ratio) but showed lower nutritional limitation (lower N:P mass ratio) than litter from more humid biomes. We found no phylogenetic signal for traits after constructing a phylogenetic tree across all biomes, suggesting that trait differences across biomes were environmentally determined. However, a strong phylogenetic signal was observed for P in the Atlantic Forest, which indicates that closely related species have similar %P in that biome. Our findings suggest that litter from more humid biomes was higher in nitrogen, although more phosphorus‐limited, than litter produced in drier climates such as that of the Cerrado biome.